PENERAPAN METODE LIMA JARI SEBAGAI INOVASI PEMBELAJARAN TAHFIDZ AL-QURAN UNTUK MENINGKATKAN DAYA HAFALAN SANTRI TAMAN PENDIDIKAN AL-QUR’AN - Samhadi, Samhadi; Suciana, Nana (Universitas Al-Amien Prenduan, 2024)
This community service activity was motivated by the problem of low memorization ability among students at the Al-Qur'an Education Park, which was caused by monotonous and uninteractive tahfidz learning methods. Many students have difficulty remembering and retaining long-term memorization because there is no strategy that combines visual, auditory, and kinesthetic aspects in the process of memorizing the Qur'an. To address this issue, the community service team applied the Five Finger Method as an innovation in Qur'an memorization learning that is easy to understand and enjoyable for children. The community service method was implemented in three stages, namely (1) socialization and training for TPA teachers on the concept and steps of implementing the Five Finger Method, (2) intensive assistance in the tahfidz learning process using this method, and (3) evaluation of students' memorization abilities through observation, interviews, and memorization tests. The approach used was participatory and collaborative, involving teachers, students, and parents as part of the learning community. The results of the community service showed a significant increase in the students' memorization abilities and motivation to learn. The students became more active, able to easily remember the order of verses, and more confident in reciting their memorization. Teachers also experienced an increase in their competence in applying creative and communicative learning methods. Overall, the application of the Five Finger Method proved to be effective as a pedagogical innovation that can improve the quality of Al-Qur'an memorization learning at TPA and strengthen the spirit of love for the Al-Qur'an among students.